Seasonal characterization and potential human health risk of heavy metals contamination in sediments of the River Jindi, Pakistan - Yousaf, Saeeda; Shakil, Muhammad; Khan, Ajmal; Ilyas, Muhammad; Jogi, Qamaruddin; Khattak, Seema Anjum; Nazneen, Shahla; Khan, Anwarzeb; Iqbal, Junaid (Journal of Himalayan Earth Sciences, 2020)
In this study, the sediments of River Jindi (Pakistan) were sampled in summer and winter to explore heavy metals contamination (i.e. Fe, Cr, Ni, Zn, Co, Cu, Pb and Cd) using Atomic Absorption Spectrophotometer. The results show that the Fe and Ni concentration was beyond the allowable limits of USEPA (2005). Water physicochemical parameters of both season showed that the concentrations of NO3, total dissolved solids (TDS) and total suspended solids (TSS) surpass the allowable levels set by the National Environmental Quality Standard and/or World Health Organization. Potential ecological risk, geo- accumulation index (Igeo), enrichment factor and contamination factor demonstrated high metals contamination in sediments and were moderately polluted with Cd and Ni. Principle component analysis indicated that in both seasons heavy metals contamination occurred through similar sources. Strong correlations (p<0.05) among heavy metals and water physicochemical parameters showed that in both seasons, physicochemical parameters played a key role in metal retention and accumulation.